Influence of ettringite on the crack self-repairing of cement-based materials in a hydraulic environment - Zhang Yanfang; Wang Anhui; Zhan Qiwei; Zhou Juanlan; Zhang Yongsheng; Gu Weiyang (Reviews on Advanced Materials Science, 2022)
As a green and environmental protection method, the self-repairing technology has great expectations to be met. In this study, the influence of ettringite on the crack self-repairing of cement-based materials in a hydraulic environment was systematically analyzed. First, the composition and pore characteristics of the self-repairing carrier was studied by XRD, XRF, and the mercury injection method. The composition was basically consistent with cement-based materials, and the structure of the self-repairing carrier was relatively dense. Second, the products were analyzed by SEM and EDS, and it was found that the distribution range of crystal size was from 1 to 20 µm, the cube and flocculent accumulation was calcite, while the rod and flake crystals were ettringite. Finally, the repair effect on the surface and inside of the crack was demonstrated by the crack area repair rate and water permeability resistance. Compared with single microbial mineralization, the synergistic repair effect of microbial mineralization and ettringite formation was better in water permeability resistance. With the further increase of water pressure, its advantages would be more obvious.